Reconstruction on the Existence of Notary Auction Officers in the Development of Auctions - Sugianto Sugianto; Abdel Salam Atwa Ali alfandi; Rizki Adi Pinandito (Jurnal Hukum, 2025)
This research focuses on the reconstruction of the position and authority of notaries as auction officials in filling the legal vacuum and strengthening the legitimacy of auction minutes. The goal is to realize legal certainty and encourage a more modern, fair, and responsive auction system that meets the needs of the community. This research uses doctrinal legal methods, relying on secondary data as library research. The research findings indicate that the existence of auction officials is still weak due to irrelevant colonial legacies, limited numbers, short terms of office, narrow authority, lack of authenticity in auction minutes, and outdated regulations and supervision. Reconstruction of the authority of auction officials from notaries is necessary to eliminate dualism, align regulations with the Notary Law, and strengthen legal certainty through the establishment of a new Auction Law that grants full authority to notaries with a certification mechanism, so that auction minutes have authentic legal force and can support the development of the auction system in Indonesia. This model adopts the pattern of appointing Notaries as Cooperative Deed Making Officials, thereby increasing professionalism and ensuring legal certainty in auction practices.